Occurrence of mycotoxins, diversity of aspergillus section flavi, along the cassava value chain, and innovative strategy for aflatoxin reduction during storage in Uganda - Oyesigye, Elias (Cranfield University, 2025)
This thesis (1) Investigated the cassava handling practices along the value chain in two contrasting cassava production and consumption regions (each with four districts) of Uganda, to identify critical points that may potentially contribute to mycotoxin contamination, understand the knowledge extent about mycotoxins, and identify and collect the major consumed cassava products, (2) determined the occurrence and distribution of mycotoxins in major cassava products to identify the levels of mycotoxin contamination along the major value chain actors (farmer and wholesaler and processors) from samples in different regions, (3) assessed the fungal diversity, and identity of dominant fungal species (Aspergillus section Flavi ) isolated from soil and cassava products from Uganda, and (4) developed an innovative strategy with potential to completely eliminate occurrence of aflatoxins during storage. One of the major outputs of this thesis was to develop a Hazard Analysis and Critical Control Point plan for the cassava value chain in Uganda. Key practices identified as likely to predispose cassava to mycotoxins contaminations include peeling cassava on bare ground, direct ground drying, inadequate storage conditions, and poor processing techniques. Data from 210 individual interviews, 34 key informants and 4 focus group discussions revealed that majority (51 %) of farmers peeled cassava directly on bare ground, resulting in direct contact with soil that potentially harbours mycotoxin-producing fungi, such as Aspergillus section Flavi. During post-harvest handling, 51.6 % of farmers dried cassava chips directly on bare ground. Nearly, all (95.2 %) of wholesalers packed cassava chips in local gunny bags and placed them on ground instead of pallets. In the processing of cassava chips into flour, only one of the 14 processing machine was certified by the Uganda National Bureau of Standards. The greatest proportion (73 %) blended cassava flour with flour from mycotoxin-susceptible crops mainly maize, millet, and sorghum. Most (96.2%) of the people along the cassava value chain did not understand what the term mycotoxins meant, but 56% were familiar with the term aflatoxins. Of the cassava value chain actors aware of mycotoxins, 82.9 % knew of methods for reducing aflatoxin contamination, but only 40.9 % were putting such methods into practise. Cassava chips and flour were the predominantly consumed cassava products by 95% of respondents and were assessed for mycotoxin contamination. A total of 192 samples of cassava products (96 flour and 96 chips) analysed using LC-MS/MS revealed that all positive samples irrespective of their origin (flour or chips), exhibited aflatoxin B1 (AFB1) levels exceeding the EU regulatory threshold of 5 µg/kg. For the first time, the study reported the highest levels of AFB1 in Uganda’s cassava, ranging from 13.1 to 298 µg/kg in flour and 2.24 to 420 µg/kg in chips. The sum of fumonisins (FB1+FB2), zearalenone (ZEN) and deoxynivalenol (DON) were significantly (P<0.05) higher in cassava flour (14.3 µg/kg; 3.71 µg/kg; 25.1 µg/kg) compared to chips (6.54 µg/kg; 1.25 µg/kg; 0.25 µg/kg), respectively. Cassava flour samples from farmers exhibited significantly (P<0.05) higher mean concentrations of AFB1 (27.1 µg/kg), total aflatoxins (78.2 µg/kg) and ochratoxin A (79.6 µg/kg) in contrast to wholesalers, at 8.91, 5.79 µg/kg and 2.44 µg/kg, respectively. The risk of AFB1 exposure to cassava consumers was also determined and revealed that, cassava consumers in Northern Uganda are at a higher risk of Hepatocellular Carcinoma (HCC)-a type of liver cancer, with an estimated 2.06 cancer cases per 100,000 individuals per year compared to those in Eastern Uganda at 0.25. Given that aflatoxins were the most dominant mycotoxins in Uganda’s cassava products, it was paramount to identify the aflatoxin producing species for targeted intervention. To identify the aflatoxin producing species in Uganda’s cassava, a total of 288 samples (soil-48, tubers-48, chips-96, and flour-96) were assessed for the number of colony forming units (CFU/g) growing on Dicloran-18-glycerol agar (DG-18). The most dominant fungi (Aspergillus section Flavi) were further assessed for its aflatoxigenicity, and a polyphasic approach was followed to identify the species. Aspergillus (84%), Penicillium (2.1%), Fusarium (3.62%), and Rhizopus (9.9%) were frequently observed fungal genera. Within the Aspergillus genus, species belonging to Aspergillus section Flavi were significantly (P=0.021) the most dominant with highest CFU/g of 1.48 ×105. A total of 77/162 (47.5%) was aflatoxigenic. 22/27 isolates from soil were aflatoxigenic, labelling it a strong reservoir for aflatoxigenic species. Following polyphasic approach, 64% (33/52) of the isolates were Aspergillus flavus, 25% (13/52) Aspergillus parasiticus, 8% (4/52) Aspergillus novoparasiticus, one Aspergillus minisclerotigenes, and another Aspergillus tamari. Three distinct Aspergillus isolates were identified, including one identified as Aspergillus tamari, which produced AFB1, AFB2, and AFG1 but not cyclopiazonic acid (CPA). In addition, two Aspergillus parasiticus isolates were found to produce only AFB1, AFB2, and CPA. These species will be sent for confirmation to Westerdijk Institute for further investigation. Thus, to manage aflatoxins in Uganda, there is need to develop innovative solutions specifically targeting Aspergillus section Flavi isolates with strong focus on Aspergillus flavus. In this study we investigated the efficacy of sodium metabisulphite on reducing aflatoxins during storage. Both in vitro laboratory and field experiments were conducted. In vitro involved growing three highly aflatoxin-producing species (A. flavus, A. parasiticus, and A. minisclerotigenes) in cassava-based media at different water activity (0.90, 0.95, 0.99 aw) at different concentrations of sodium metabisulphite (0, 125, 250, 500, 1250, 1500 mg/L) for 15 days. While field experiments were set up in Uganda’s field conditions in districts with different climatic conditions. The initial fungal load, and AFB1 levels were determined. In vitro results showed that NaMBS completely inhibited the growth of A. flavus, A. parasiticus, and A. minisclerotigenes—reducing growth (colony diameters) from 48 mm, 45 mm, and 20 mm, respectively, to zero—at a concentration of 1250 mg/L of sodium metabisulphite. Field experiments were set up in Uganda’s field conditions in districts with varying climatic conditions. The initial fungal load, and AFB1 levels were determined. The results in field conditions revealed that NaMBS had a significant potential in reducing both the fungal load and completely reducing initial AFB1 concentration. Cassava chips placed in traditional bags without NaMBS treatment showed the highest levels of AFB1 levels (146.6 µg/kg) and fungal load of 20.4 mean cfu/g ×10^5 indicating that traditional bags, when untreated with NaMBS, do not significantly reduce AFB1 and fungal load. While PICS bags without NaMBS treatment also exhibited a considerable amount of AFB1 (91 µg/kg) and fungal load of 6.1 mean cfu/g ×10^5. However, the application of NaMBS treatment led to a drastic reduction in AFB1 from 185 µg/kg to 10.9 µg/kg (94.5% reduction rate) and fungal load 3.5 mean cfu/g ×10^5(82.8% fungal reduction) for traditional bags and 0.23 µg/kg (99.9% reduction rate) and fungal load of 1.9 mean cfu/g ×10^5 for PICS bags. These findings suggest that the addition of NaMBS treatment is highly effective in reducing the fungal load and AFB1 in both types of bags. This thesis provides a major contribution towards management of mycotoxins especially aflatoxins within cassava production in Uganda. Finally, based on Hazard Analysis and Critical Control Point (HACCP), out of the six main steps of cassava flour production which include harvesting, peeling, milling, storage, packaging and drying, the critical control points are: storage, packaging, and drying on bare ground. Harvesting, peeling and milling are not critical control points (CCPs) but possess potential areas of contamination that should be prevented. Key ecophysiological factors that should be monitored to manage the CCPs below the control limits include moisture content (ideally below 13%), water activity (aw between >0.6), and relative humidity (preferably below 65%). Also, total aflatoxin levels should be kept below 10 µg/kg. Implementing good handling practices and good agronomic practices are also vital to manage these CCPs.
Cervini, Carla - Associate Supervisor
Keywords: occurrence and distribution of mycotoxins; levels of mycotoxin contamination; major value chain actors; fungal diversity; eliminate occurrence of aflatoxins during storage; processing techniques